Exploring the synergistic effects of Life’s Essential 8, insulin resistance, and CRP on cardiometabolic multimorbidity risk - Liu, Jiang; Yang, Chuang; Cheng, Wenke; Li, Daidi (Frontiers in Nutrition, 2025)
BackgroundCardiometabolic multimorbidity (CMM) refers to the co-occurrence of two or more cardiometabolic diseases (CMDs), including coronary artery disease (CAD), stroke, and type 2 diabetes mellitus (T2DM), posing a substantial public health concern. Although Life’s Essential 8 (LE8), a cardiovascular health (CVH) metric incorporating behavioural and metabolic factors, has been developed, its relationship with CMM remains unexplored. This study examines the independent and combined effects of LE8, insulin resistance (IR) and C-reactive protein (CRP) on CMM risk.MethodsIn this prospective cohort study, 304,568 UK Biobank participants without CMM at baseline were followed. The association between LE8 and CMM risk was assessed using Cox proportional hazards models, and dose–response relationships were evaluated using restricted cubic splines. Mediation analyses were conducted to determine the roles of triglyceride-glucose index (TyG, an IR indicator) and CRP in mediating the LE8-CMM association.ResultsOver a 14.2-year follow-up, 5,441 participants developed CMM. Higher LE8 scores were significantly associated with reduced CMM risk (hazard ratio [HR] per 10-point increase: 0.65; 95% confidence interval [CI]: 0.63–0.67). Accelerated failure time models indicated that increased LE8 scores delayed CMM onset by up to 47.3 months. Mediation analyses showed that TyG and CRP accounted for 18.8 and 2.9% of LE8’s protective effect on CMM, respectively.ConclusionMaintaining high LE8 scores is associated with a lower risk of developing CMM, partially mediated by reductions in IR and inflammation. Promoting CVH and addressing metabolic and inflammatory factors may help prevent CMM and reduce its burden on public health.